Another mistaken case of appendicitis. (26th October 2015) - Laji, Nidhin; Bowyer, Richard; Jeyaratnam, Dakshika; Zuckerman, Mark
Abstract : In 2010, when I was 17, I presented to hospital with progressive discomfort and pain in the right iliac fossa when eating and moving, associated with mild fever and diarrhoea. Appendicitis was suspected but immediate surgery was deferred, as the inflammatory markers did not adequately support the clinical diagnosis of appendicitis. Further tests, including MRI, were then undertaken. The MRI showed evidence of terminal ileitis and a normal appendix. Crohn's disease was considered as part of the differential diagnosis. However, a Yersinia enterocolitica infection was subsequently confirmed. The episode highlighted several learning points including preventing unnecessary surgery and the advantages of using a multidisciplinary approach involving imaging the abdomen and microbiological input.